Cross-cultural Differences Experienced during Hajj: A Case Study of Acehnese Hajj - Bustamam-Ahmad, Kamaruzzaman; Zakaria, Rahmi (Studia Islamika, 2018)
The cross-cultural differences experienced by pilgrims during the world’s largest religious ritual, ḥajj, have yet to be explored. It is worthwhile to investigate this issue from an Indonesian perspective. This study uses a phenomenological approach to examine cross-cultural differences experienced by Acehnese pilgrims during ḥajj. The perceptions of Acehnese who have never been to Mecca (‘villagers’) and Acehnese who stayed in Saudi Arabia and its neighbouring countries (‘stayers’) were also probed. The findings show that the pilgrims experienced cross-cultural differences in verbal communication, body movement, physical appearance and dress, the use of space, time, touch, voice, and smell. Cross-culturally, the pilgrims have a different perspective to villagers and stayers. The pilgrims expressed culture shock, while the villagers’ perceptions were primarily shaped by imagined and unverified stories, and the stayers understood their pilgrimage through their long experiences of residing in Arab countries.DOI: 10.15408/sdi.v25i1.5356